Faktor-Faktor Tingkat Kepuasan Tenaga Kerja terhadap Produktivitas Sales Promotion Girl (SPG) pada PT. Garuda Inovasi Semesta (Komplit) Bandar Lampung - Sutadipraja, Edwin; Asmuni, Idris (Jurnal Enterpreneur dan Bisnis (JEBI), 2022)
This study aims to obtain empirical evidence on the influence of salaries, incentives and education on performance productivity. "Case Study in the company of PT Garuda Inovasi Semesta (Komplit) in Bandar Lampung, Lampung - Indonesia. The independent variables used in this research are salary (X1), incentive (X2), and Education (X3), and dependent variable that is Performance Productivity (Y). This study uses primary data in the form of kuisoner spread in the company of PT. Garuda Inovasi Semesta (Komplit) in Bandar Lampung, Lampung - Indonesia. The questionnaire also comes with simple and clear filling instructions to help the respondent complete the filling. Based on the results of research and discussion, the conclusion that can be taken is a positive salary variable in this study has a positive and significant impact on productivity performance. The positive incentive variable in this study did not have a positive and significant effect on performance productivity. Positive education variable in this research have positive and significant influence to performance productivity.